Innovative Hydrogels with Silver Nanoparticles: Synthesis and Applications - Katarzyna Sala; Magdalena Bańkosz; Anna Sobusiak; Claudia Garbowska; Magdalena Kędzierska; Bozena Tyliszczak (Proceedings)
Recent years have seen significant progress in the field of hydrogel materials, especially in terms of their modification with silver nanoparticles [...]